Anthocyanins from purple sweet potato (Ipomoea batatas (L.) Lam.) and their color modulation by the addition of phenolic acids and food-grade phenolic plant extracts. (15th November 2017) - Gras, Claudia C.; Nemetz, Nicole; Carle, Reinhold; Schweiggert, Ralf M.
Highlights: An outstandingly anthocyanin-rich purple sweet potato provenance is reported. Adding co-pigments to anthocyanins allowed color modulation of aqueous solutions. Purplish-blue, light pink, magenta, brick-red, and intense red hues were observed. Rosemary extract addition enhanced p K H -values of anthocyanins from 3.28 to 4.71. Abstract: Anthocyanin profiles and contents of three purple sweet potato provenances were investigated by HPLC-DAD-MS n . In contrast to widely uniform profiles, the contents of total (558–2477 mg/100 g DM) and individual anthocyanins varied widely. Furthermore, quantitative and qualitative effects of intermolecular co-pigmentation were studied by adding chlorogenic and rosmarinic acids, and food-grade phenolic apple and rosemary extracts at various dosages to a diluted purple sweet potato concentrate at pH 0.9, 2.6, 3.6, and 4.6. Addition of co-pigments generally increased p K H estimate -values of anthocyanins from 3.28 (without co-pigments) to up to 4.71, thus substantially broadening the pH range wherein colored forms prevail. The most pronounced hyperchromic shift by up to +50.5% at the absorption maximum was observed at pH 4.6. Simply by blending the co-pigments with purple sweet potato anthocyanins at pH-values ranging from 2.6 to 4.6, purplish-blue, light pink, magenta, brick-red, and intense red hues were accessible as expressed by CIE-L ∗ a ∗ b ∗ color values.